(untitled) (Research, Society and Development, 2021)
Zoology is the area of ​​Biology that is concerned with studying the life of animals, in relation to their taxonomic, phylogenetic, ecological and morphophysiological aspects. Endowed with many terms, this area is seen by many students as difficult to contextualize. In order to overcome this problem, the present work has as main objective to present and discuss the potentialities of the film “Arachnophobia”, as well as, to present it as a didactic resource to explore themes of Zoology aiming to contribute in the process of students’ learning in the discipline of Biology in high school. In this way, through the proposed film, the teacher will be able to work with students on the whole structure and function of spiders, as well as discuss and problematize questions about venomous animals and instruct students on good practices to avoid accidents with these organisms in their houses. Another interesting issue is the opportunity to bring information to students about accidents with these animals, a fact that occurs routinely throughout Brazil. In addition, this activity can be an integrating axis to arouse students’ interest on issues related to conservation, species preservation, and even the ecological relationships of spiders in the ecosystem.